Co film stretching induced by lattice mismatch and annealing : The role of Graphene - Carlomagno, I.; Drnec, J.; Vlaic, S.; Vinogradov, Nikolay ; 0000-0002-1477-853X; Carlà, F.; Isern, H; Meneghini, C.; Felici, R. (Applied Surface Science, 2018)
Thin Co films intercalated between a Graphene capping layer and the Ir(111) surface are of interest for spintronics applications due to their peculiar magnetic properties and to their chemical stability. The structure, and then the magnetic properties, of the Co films depend on the intercalation process which is strongly influenced by the temperature, total amount of Cobalt and quality of the capping Graphene layer. In order to identify and disentangle the effects of these contributions, we report on the structural characterisation of four Co films as a function of thickness, annealing temperature, and Graphene capping. From the structural point of view, the deposition of Co on a hot Ir substrate mimics quite well the intercalation process proving the validity of the colander model describing the Graphene role during the process.
Keywords: Graphene; Intercalation; Thin films